Crack growth threshold under hold time conditions in DA Inconel 718 – A transition in the crack growth mechanism (Fracture and Structural Integrity, 2015)
Aeroengine manufacturers have to demonstrate that critical components such as turbine disks, made of DA Inconel 718, meet the certification requirements in term of fatigue crack growth. In order to be more representative of the in service loading conditions, crack growth under hold time conditions is studied. Modelling crack growth under these conditions is challenging due to the combined effect of fatigue, creep and environment. Under these conditions, established models are often conservative but the degree of conservatism can be reduced by introducing the crack growth threshold in models. Here, the emphasis is laid on the characterization of crack growth rates in the low ?K regime under hold time conditions and in particular, on the involved crack growth mechanism. Crack growth tests were carried out at high temperature (550 °C to 650 °C) under hold time conditions (up to 1200 s) in the low ?K regime using a K-decreasing procedure. Scanning electron microscopy was used to identify the fracture mode involved in the low ?K regime. EBSD analyses and BSE imaging were also carried out along the crack path for a more accurate identification of the fracture mode. A transition from intergranular to transgranular fracture was evidenced in the low ?K regime and slip bands have also been observed at the tip of an arrested crack at low ?K. Transgranular fracture and slip bands are usually observed under pure fatigue loading conditions. At low ?K, hold time cycles are believed to act as equivalent pure fatigue cycles. This change in the crack growth mechanism under hold time conditions at low ?K is discussed regarding results related to intergranular crack tip oxidation and its effect on the crack growth behaviour of Inconel 718 alloy. A concept based on an “effective oxygen partial pressure” at the crack tip is proposed to explain the transition from transgranular to intergranular fracture in the low ?K regime.
Keywords: Inconel 718; Fatigue crack growth; Crack growth threshold; Intergranular to transgranular transition